200 Years of Parkinson's disease: what have we learnt from James Parkinson?. (5th January 2018) - McDonald, Claire; Gordon, Gavin; Hand, Annette; Walker, Richard W; Fisher, James M
Abstract: 2017 marks 200 years since James Parkinson's published his 'Essay on the Shaking Palsy'. Although now most famous for describing the condition that came to bear his name, Parkinson had a wide range of interests and his influence spread beyond medicine. In this review, we provide a biography of James Parkinson's remarkable life. Parkinson's paper not only comprehensively described the symptoms of Parkinson's disease (PD), but challenged his peers to better understand the pathophysiology of the PD. Key observation over the next 2 centuries, included the recognition of the link between the substantia nigra and PD and the discoveries of dopamine deficiency in patients with PD. We review the subsequent development of pharmacological and surgical therapies. Despite great progress over the last 200 years, Parkinson's hopes for a 'cure if employed early enough' or that 'some remedial process may ere long be discovered by which at least the progression of the disease may be stopped' remain apposite today and we reflect on the challenges ahead for the next century.